Does the rural social pension alleviate urban-rural health inequality of opportunity? Evidence from China - Qin, Cheng; Zhao, Jing; Liu, Jianyi (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: To examine the impact of the New Rural Pension Scheme (NRPS) on health disparities between the urban and rural elderly in China. Methodology: The authors constructed health inequality of opportunity (IOp) based on the ex-ante principle and utilised panel data from the China Health and Retirement Longitudinal Study (2015-2018), employing both difference-in-differences (DID) and propensity score matching DID methodologies to assess the impact. Results: It was found that enrolment in the NRPS significantly enhanced health levels of the rural elderly and reduced health inequality of opportunity between the urban and rural elderly by 6.67%. The impact was more pronounced among lower-income and older age groups. Implications and recommendations: The findings suggest that targeted social pension programmes can effectively reduce regional health disparities. Future research should explore the long-term sustainability of these effects and their applicability to other developing countries with similar urban-rural divides. Originality/value: This study uniquely applied inequality of opportunity theory to distinguish between ‘justifiable’ and ‘unjustifiable’ health disparities, providing a more comprehensive understanding of urban-rural health inequalities and demonstrating the effectiveness of social pension programmes in addressing these disparities. Keywords: health inequalities, social pension, inequality of opportunity (IOp), urban-rural disparities
Argumenta Oeconomica, 2025, Nr 2 (55), s. 34-51
Keywords: health inequalities; social pension; inequality of opportunity; urban-rural disparities